The effect of cryoprotectant and equilibration period on quality and fertility of duck and muscovy sperm - Setioko, A.R; Situmorang, P; Triwulanningsih, E; Sugiarti, T; Kusumaningrum, D.A (Indonesian Animal Sciences Society, 2002)
The study was conducted to evaluate the effect of cryoprotectant and equilibration period on quality and fertility of duck and muscovy spermatozoa. Semen collected from Alabio and muscovy drakes was diluted using three different cryoprotectants:glycerol, DMSO and DMF, thereafter the semen was equilibrated 50C for 15; 30 and 60 minutes then frozen and stored in liquid nitrogen, designed by factorial 3 x 3. After thawing, semen sample was investigated on the motility and mortality rate. The best cryoprotectant and equilibration period was used in fertilization test. Duration of fertility was calculated from the second day after insemination until the last fertile egg, and the percent of fertility was calculated from the second day until the forth day after insemination. The use of cryoprotectant significantly affected sperm motility after freezing. The use of glycerol as a cryoprotectant was the lowest (P<0.05) compared to DMSO and DMF. Similarly, duck sperm motility after being freezed with glycerol, DMF and DMSO were 9.02; 21.75, and 32.86%, and for muscovy sperm motility were 11.78; 32.45 and 34.92% respectively. The percentage of live sperm for duck were 23.84; 40.14 and 42.20, while for muscovy were 29.26; 53.06 and 51.80 respectively after being freezed with glycerol, DMF and DMSO. Equilibration period did not affect the percentage of live sperm after freezing. Results of this study showed that duration of fertility of Alabio duck after being inseminated with fresh drake semen was longest compared to that of insemination using fresh muscovy semen, frozen drake semen and frozen muscovy semen (4.96 vs 3.5; 2.4 and 1.5 days respectively). Results from this study clearly indicated that preservation of sperm reduced the quality of spermatozoa. It is suggested that freezing technique of both duck and Muscovy sperm could be conducted using DMF or DMSO as a cryoprotectant with the equilibration period between 15 to 60 minutes. Â Key words: Sperm, cryoprotectant, fertility, AI, duck, muscovy